Advances in Urban Lifestyle and Technology. - Suparta, Wayan (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2021)
Cities, with all their complexities, grow as engines of development, especially in the fields of sociology, economy, and technology. As they shape the character of people, smart cities that implement strategies for sustainable urban development are a necessity. This book addresses various issues concerning urban lifestyle phenomena affecting the social economy and technological needs such as governance of sustainable urban development, green technology, and the environment. It will be a useful reference for local stakeholders when making appropriate policy and planning choices to protect the e.
Intro -- Table of Contents -- Preface -- Section I -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Section II -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Section III -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Chapter 12 -- Chapter 13 -- Chapter 14 -- Chapter 15 -- Section IV -- Chapter 16 -- Chapter 17 -- Chapter 18 -- Chapter 19
Print version record.
eBooks on EBSCOhost
Keywords: City planning; Sustainable urban development; Green technology; Urbanisme durable; Technologie de protection de l'environnement.; Urban communities; Sustainability; Social issues: environment & green issues (Children's / Teenage).; City planning; Green technology; Sustainable urban development